Comparative analysis of surgical costs vs. theoretical tiopronin therapy in pediatric cystinuria: a single-center experience from Türkiye - Sözduyar, Sümeyye; Ulman, Hilmican; Tekin, Ali; Ulman, İbrahim and Tiryaki, Sibel (The Turkish Journal of Pediatrics, 2026)
Background. Cystinuria is a rare autosomal recessive disorder leading to recurrent cystine stone formation, often necessitating repeated surgical interventions. In Türkiye, tiopronin—a proven medical therapy—has become inaccessible since 2019, raising concerns about its economic and clinical consequences. This study aimed to compare the annual hospital costs of surgical management with the theoretical cost of tiopronin therapy in pediatric cystinuria patients. Methods. This single-center, retrospective study included 10 consecutive pediatric patients (median age: 12 years; range: 3-17 years) with genetically or biochemically confirmed cystinuria who underwent surgery for cystine stones in 2023. The annual cost of surgical management was calculated by summing all direct medical costs (operating room, anesthesia, devices, hospitalization, and related diagnostics) obtained from the hospital billing database. The theoretical annual cost of tiopronin therapy was calculated based on the last accessible market price of the drug in Türkiye, converted to Turkish Lira at the 2023 average exchange rate, and adjusted per patient using a standard dosing regimen of 15 mg/kg/day. Costs were compared using the Mann-Whitney U test. Results. The median annual surgical cost per patient was 49,936 TL (range: 14,791–84,576 TL), compared to a theoretical tiopronin cost of 27,923 TL (range: 9,307–27,925 TL). Surgical management was significantly more expensive than tiopronin therapy (p=0.001) in 9 of 10 cases. Six patients had a history of tiopronin use, and five of them experienced a surgery-free interval during medication (median duration: 3 years; range: 2-6 years). Preliminary follow-up data for 2024 revealed that 70% of patients required further surgical interventions (median: 2 surgeries per patient), demonstrating the persistent and recurrent nature of the disease when managed solely with surgery. Conclusion. Surgical treatment of cystinuria poses a substantially higher economic burden compared to tiopronin therapy. Our findings support the reintroduction of tiopronin into the Turkish healthcare system, particularly for pediatric patients with frequent stone recurrence.